THE INFLUENCE OF THE SCHOOL PRINCIPAL'S COACHING APPROACH ON TEACHER PERFORMANCE IN THE IMPLEMENTATION OF STUDENT-SIDED LEARNING - Ambarwati, Puji; Qurtubi, Ahmad (Journal of Educational Administration, 2023)
This study aims to explore and analyze the influence of the principal's coaching approach on teacher performance in the context of the application of student-centered learning. Coaching here refers to a method of professional development that involves support and guidance from the principal to the teacher. The main focus of research is to understand the extent to which coaching approaches can make a positive contribution to the quality of teacher teaching in creating learning environments that suit the individual needs of students. The research method used is a quantitative approach with an experimental research design. Data analysis was conducted to evaluate significant changes in teacher performance and their impact on the implementation of pro-student learning. The results showed that the principal's coaching approach had a positive influence on teacher performance in the context of implementing pro-student learning.